ARE CARIOGENIC BACTERIA THE MAJOR RISK FACTOR TO DENTAL CARIES IN PATIENTS WITH ULCERATIVE COLITIS? - RODRIGUES,Eduardo (2019)
ABSTRACT BACKGROUND: High prevalence of dental caries in ulcerative colitis (UC) has been attributed to diet and changes in salivary environment. OBJECTIVE: We aimed to characterize the prevalence of dental caries, salivary flow rates, salivary buffering capacity and cariogenic bacteria counts of Mutans streptococci and Lactobacillus spp and to evaluate their relationship with drug therapy, disease activity and duration. METHODS: A cross-sectional study was performed with UC patients followed in a tertiary center. Participants were submitted to a questionnaire (including demographic data, oral hygiene, eating habits) and a clinical observation with assessment of plaque index and Decayed, Missing and Filled Teeth index. Unstimulated/stimulated saliva was collected. Medical records, disease activity (Partial Mayo Score) and disease duration were collected. Laboratory data included salivary flow rates, salivary buffering capacity (CRT® buffer) and cariogenic bacteria count (Mutans streptococci and Lactobacillus spp) in saliva using the CRT® bacteria test (results: high or low counts). RESULTS: Thirty UC patients were recruited. Oral hygiene routines were daily teeth brushing once or more (96.7%) and fluoride toothpaste (73.3%). Decayed, Missing and Filled Teeth index (mean 16.17±6.428) was not affected by the frequency of soft drinks, cakes, sweets and sugars between meals (P>0.2). Long-term disease showed a trend towards higher prevalence of caries (P=0.06). Most presented normal salivary flow rates, unstimulated (73.3%) and stimulated (60.0%), and high salivary buffering capacity (66.7%). Any association was found with age, gender, disease activity, disease duration and drug therapy. High Mutans streptococci and low Lactobacillus spp count were observed in 73.3% and 60% of patients, respectively. Patients with active disease (100%) and longer duration (88.9%) displayed higher Mutans streptococci count. CONCLUSION: The prevalence of dental caries observed in UC patients was significant and did not seem to be influenced by their eating habits. The high prevalence of Mutans streptococci count may be a major risk factor for dental caries and may be looked as part of the UC dysbiosis. Dental care of UC patients should be planned according with this microbiota variation.